Analyzing Ecological Data - Zuur, Alain; Ieno, Elena N.; Smith, Graham M. (Statistics for Biology and Health, 2007)
This book provides a practical introduction to analysing ecological data using real data sets collected as part of postgraduate ecological studies or research projects. The first part of the book gives a largely non-mathematical introduction to data exploration, univariate methods (including GAM and mixed modelling techniques), multivariate analysis, time series analysis (e.g. common trends) and spatial statistics. The second part provides 17 case studies, mainly written together with biologists who attended courses given by the first authors. The case studies include topics ranging from terrestrial ecology to marine biology. The case studies can be used as a template for your own data analysis; just try to find a case study that matches your own ecological questions and data structure, and use this as starting point for you own analysis. Data from all case studies are available from www.highstat.com. Guidance on software is provided in Chapter 2. Alain Zuur is senior statistician and director of Highland Statistics Ltd., a statistical consultancy company based in the UK. He has contributed to a wide range of projects related to marine biology, oceanography, ecology, fisheries, etc. and has extensive experience teaching statistics to ecologists and environmental scientists in the form of academic and non-academic courses. He is honorary research fellow in the School of Biological Sciences, Oceanlab, at the University of Aberdeen, UK. Elena Ieno is senior marine biologist at Highland Statistics Ltd. In 2004 she left academia to work full time in statistical consultancy. She now teaches statistics to ecologists and has shown she can bridge the gap between the two disciplines and dispel the dread of statistics shown by most biologists. She is also involved in various international statistical consultancy projects, and is honorary research fellow in the School of Biological Sciences, Oceanlab, at the University of Aberdeen, UK. Graham M. Smith is a Senior Lecturer at Bath Spa University in the UK where he teaches statistics to biology undergraduates. He has a background in ecological consultancy, and continues to provide consultancy on the design and analysis of ecological monitoring programmes and the development of quantitative methods in Ecological Impact Assessment.